2011
DOI: 10.1212/wnl.0b013e3182166df5
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory copy number association with age at onset of Alzheimer disease

Abstract: MoCA (90%; CI 82%-95%). It is unlikely that the specificity of the SCOPA-COG for the PD-N vs PD-MCI comparison would improve with a larger sample for a screening cutoff because this instrument is sensitive to minor impairments evident in the PD-N group (table 2). 1Relative to the values given for the whole sample in table 3, 1 no diagnostic performance values worsened and some improved when the MoCA analysis was restricted to those patients with PD-N and patients with PD-MCI who were tested on both the MoCA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…In addition, a higher copy number of a complex multiallelic segment (DGV variation_0316) containing the olfactory receptor genes on chromosome 14q11.2 was reported to be associated with a decrease in age at onset of AD using genotypes obtained from Affymetrix SNP 6.0 arrays (controls were not evaluated) (Shaw et al 2011). Although this region is 200 kb in size, it is poorly covered with SNPs in the 650Y array used for our study (three SNPs).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, a higher copy number of a complex multiallelic segment (DGV variation_0316) containing the olfactory receptor genes on chromosome 14q11.2 was reported to be associated with a decrease in age at onset of AD using genotypes obtained from Affymetrix SNP 6.0 arrays (controls were not evaluated) (Shaw et al 2011). Although this region is 200 kb in size, it is poorly covered with SNPs in the 650Y array used for our study (three SNPs).…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, it is precisely at this stage that the clinical diagnosis is most difficult. Recently, the possibility of using olfaction as a biomarker for AD has been explored in both patients (Shaw et al, 2011;Schofield et al, 2012) and animal models (Wesson et al, 2010;Kameshima et al, 2012). Our current data using an AD model that is specifically olfactory-based, indicate that olfactory behavior can indeed provide effective insight into the circuit organization of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies investigating multiple assay protocols for plasma A β in different laboratories found very good reproducibility of values (Okereke et al 2009). While this has not necessarily been the case for CSF measures (Mattsson et al 2011), a recent ADNI round-robin study of CSF tau and A β showed very good inter-lab reproducibility (Shaw et al 2011). …”
Section: Variables That Affect Plasma Aβmentioning
confidence: 99%